Cardiac procedural myocardial injury, infarction and mortality in patients undergoing elective PCI: a pooled analysis of patient-level data. (25th November 2020) - Silvain, J; Zeitouni, M; Paradies, V; Zheng, H; Ndrepepa, G; Cavallini, C; Feldman, D.N; Sharma, S.K; Mehilli, J; Jaffe, A.S; Thygesen, K; Montalescot, G; et al.
Abstract: Background: The prognostic implications of cardiac procedural myocardial injury and infarction (MI) in chronic coronary syndrome patients undergoing elective percutaneous coronary intervention (PCI) is still debated. Objective: To determine the optimal cardiac troponin threshold for identifying prognostically important events. Methods: Using a pooled dataset of nine registries and one randomized trial, we analysed individual data of 14, 433 patients undergoing elective PCI with a normal or moderately elevated baseline pre-PCI cardiac troponin (cTn). A multivariate model was performed to evaluate the associations between post-PCI cTn elevation and 1-year mortality after PCI, including thresholds used by existing procedural myocardial injury definitions (Fourth Universal Definition of MI [UDMI] and Academic Research Consortium 2 [ARC-2] / Society for Cardiovascular Angiography and Interventions (SCAI)). The association between type 4a MI and 1-year mortality was also evaluated. Results: Procedural myocardial injury defined by the Fourth UDMI occurred in 52.5% of patients and was not associated with 1-year mortality (adjOR 1.27, 95% CI [0.90–1.81] p=0.18). The association between post-PCI cTn elevation and 1-year mortality was significant above a 3-fold increase above the upper reference limit, and was optimal for a 5.2-fold increase which corresponded to an 18.3% rate of event, and an adjOR of 2.03 (95% CI [1.31–3.14], p=0.002) (figure). Procedural myocardial injury defined by the ARC-2/SCAI definition occurred in 1.3% of the patients, had a strong association with 1-year mortality (adjOR 4.15, 95% CI [1.62–10.64], p<0.01) but lacked sensitivity (5.2% sensitivity). Type 4a MI occurred in 12.7% of patients, was strongly associated with 1-year mortality (adjOR 3.18, 95% CI [1.47–6.90], p=0.002), but could only be evaluated in a subset of patients (n=3 084) with available data on new myocardial ischaemia post-PCI. Conclusions: We have demonstrated that a post-PCI cTn elevation ≥5x the 99th percentile URL in CCS patients with normal baseline cTn, represents the optimal threshold for defining prognostically important or "Major" procedural myocardial injury in the absence of evidence for new myocardial ischaemia. Major procedure related myocardial injury and type 4a MI should be considered as a quality metric and endpoints in clinical trials. Funding Acknowledgement: Type of funding source: None